Comparison between findings of saline infusion sonohysterography and office hysteroscopy in patients with recurrent implantation failure - Ahmed Reda; Ahmed Sherif Abdel Hamid; Rowaa Mostafa; Eman Refaei (Wolters Kluwer Medknow Publications, 2016)
Aim: This study aims to determine the accuracy of saline infusion sonohysterography (SIS) in the diagnosis of intrauterine pathologies in women with recurrent implantation failure (RIF). Settings and Design: This is a prospective cross-over study which was carried out during the period between December 2013 and July 2014. Materials and Methods: The study involved sixty subfertile women with a history of RIF. All cases underwent a transvaginal ultrasonography, SIS and then an office hysteroscopy (1 day after SIS) during early follicular phase. SIS was carried out by same sonographer, and then hysteroscopy was carried out by same gynecologist who was kept blind to findings at SIS. Statistical Analysis: Was done using IBM© SPSS© Statistics version 22. The sensitivity of SIS was calculated as it equals: True positive by SIS/all positive (true cases by hysteroscopy) and specificity was calculated as it equals: True negative by SIS/all negatives (normal by hysteroscopy). Results: Overall uterine abnormalities were significantly less likely to be identified with SIS compared to hysteroscopy (P = 0.002), but analysis of each finding separately demonstrated a comparable difference between SIS and hysteroscopy (P > 0.05). We found that the sensitivity, specificity, positive predictive value, and negative predictive value of SIS to detect intrauterine pathology is 41.2%, 100%, 100%, and 81.1%, respectively. Conclusion: Our findings suggest a good role of SIS in the workup for RIF saving more invasive procedure for selected cases.